Theban Harbours and Waterscapes Survey, 2014*. Issue 1 (January 2014) - Graham, Angus; Strutt, Kristian D.; Hunter, Morag A.; Pennington, Benjamin T.; Toonen, Willem H. J.; Barker, Dominic S.
Report on the 2014 season of the Theban Harbours and Waterscapes Survey. The paper discusses topographic survey and data correction for the West Bank of Thebes and geoarchaeological investigation of the Temple of Millions of Years of Amenhotep III and the area to the east of the Ramesseum.